Reassortment of high-yield influenza viruses in vero cells and safety assessment as candidate vaccine strains - Jian Zhou; Fan Yang; Jinghui Yang; Lei Ma; Yina Cun; Shaohui Song; Guoyang Liao (Human Vaccines & Immunotherapeutics, 2017)
Vaccination is the practiced and accessible measure for preventing influenza infection. Because chicken embryos used for vaccine production have various insufficiencies, more efficient methods are needed. African green monkey kidney (Vero) cells are recommended by the World Health Organization (WHO) as a safe substitute for influenza vaccine production for humans. However, the influenza virus usually had low-yield in Vero cells, which limits the usage of Vero cellular vaccines. This study used 2 high-yield influenza viruses in Vero cells: A/Yunnan/1/2005Va (H3N2) and B/Yunnan/2/2005Va (B) as donor viruses. It used 3 wild strain viruses to reassort new adaptation viruses, including: A/Tianjin/15/2009(H1N1), A/Fujian/196/2009(H3N2), and B/Chongqing/1384/2010(B). These three new viruses could maintain the characteristic of high-yield in Vero cells. Furthermore, they could keep the immunogenic characteristics of the original wild influenza viruses. Importantly, these viruses were shown as safe in chicken embryo and guinea pigs assessment systems. These results provide an alternative method to produce influenza vaccine based on Vero cells.